1993
DOI: 10.1172/jci116796
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress differentially modulates expression of genes encoding basic fibroblast growth factor and platelet-derived growth factor B chain in vascular endothelium.

Abstract: Fluid shear stress has been shown to be an important regulator of vascular structure and function through its effect on the endothelial cell. We have explored the effect of shear stress on the expression of the heparin-binding growth factors platelet-derived growth factor B chain (PDGF-B) and basic fibroblast growth factor (bFGF) in bovine aortic endothelial cells using a purpose-built cone-plate viscometer. Using morphometric analysis, we have mimicked the endothelial cell shape changes encountered in vivo in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(148 citation statements)
references
References 49 publications
4
142
1
1
Order By: Relevance
“…The modulation is mediated in part by the regulation of genes encoding for many proteins including vasoactive substances, growth factors and protooncogenes [15,33,47,60], affecting cell structure and function in endothelium [21,48]. Recent studies have shown that shear stress affected the brain endothelial cell surface [20,43,70].…”
Section: Discussionmentioning
confidence: 99%
“…The modulation is mediated in part by the regulation of genes encoding for many proteins including vasoactive substances, growth factors and protooncogenes [15,33,47,60], affecting cell structure and function in endothelium [21,48]. Recent studies have shown that shear stress affected the brain endothelial cell surface [20,43,70].…”
Section: Discussionmentioning
confidence: 99%
“…Within vessels containing both an inlet and outlet, shear forces on the endothelial cells are key regulators of vascular segment survival (Meeson, 1996;Azmi and O'Shea, 1984). Low flow rates in EC cultures have been shown to result in alterations in the distribution of cytoskeletal proteins (Dardik, 2005) and morphology (Malek, 1993) and induction of tissue factor expression, the cell surface initiator protein for the haemostatic cascade. In addition, cultures exposed to physiologically low rates of flow yield gene expression profiles similar to endothelium from atherosclerotic-prone arteries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The ss activates a number of intracellular signals, such as de novo transcription of growth factors (platelet-derived growth factor, transforming growth factor-␤) 46,47 or vasoconstrictors such as endothelin. 48 Integrins, which are mechanosensors of ss, prompt tyrosine kinase-related intracellular signals 49 ; however, several conditions have to be fulfilled for signaling: integrin aggregation, integrin presence, tyrosine kinase activity with phosphorylation of FAK, and actin cytoskeletal integrity, with the latter 2 addressed in this study.…”
Section: Discussionmentioning
confidence: 99%